PENGARUH POSISI TELUR AYAM KAMPUNG (Gallus gallus domesticus) PADA PROSES PENETASAN TERHADAP MORTALITAS DAN DAYA TETAS - Syarif alfikri; Doso Sarwanto; Yanita Mutiaraning Viastika; Tri Sukmaningsih (Fakultas Peternakan. Unwiku, Purwokerto, 2023)
This study aims to determine the effect of free-range chicken (Gallus gallus domesticus) egg position using 60 free-range chicken eggs which are placed in an incubator with a capacity of 100 eggs and has been carried out from March 3 to March 26, 2023. This research used an experimental method with a completely randomized design (CRD) in a unidirectional pettern consisting of four treatments, namely P1 (egg position 0º), P2 (egg position 30º), P3 (egg position 60º), P4 (egg position 90º). Each treatment consists of 5 repetitions. Parameters measured were mortality and hatchability. The results showed that the effect of egg position did not show a significant effect (P>0.05) on mortality and hatchability. Position of the eggs at 60º results in low mortality and produces a fairly good hatchability. Keywords : chicken eggs, egg position, mortality, hatchability